Enhancing mitigation and finance reporting Building on current experience to meet the Paris Agreement requirements - Vallejo, Lola (OECD Publishing, 2017)
The future enhanced transparency framework outlined in the Paris Agreement and its accompanying Decision is to build on, enhance and eventually supersede the existing measurement, reporting and verification (MRV) system established under the Cancún Agreements. This paper explores the issues of "building on" and "enhancing" as they relate to the biennial reporting of information on mitigation and finance, by drawing lessons from the existing MRV system and examining the Paris Agreement's provisions. It examines four areas: greenhouse gas (GHG) inventories, reporting on progress with the mitigation component of nationally determined contributions (NDCs), finance provided and mobilised, and financial support received and needed. The paper also highlights the challenges met by Parties while reporting information for these areas to date, and provides suggestions on how forthcoming modalities, procedures and guidelines (MPGs) might reduce these difficulties
Keywords: Energy; Environment